Applicability of training with vascular occlusion to increase hypertrophy and muscle strength: a review study - Guimarães, Brenda Mendonça; Alves, Rafael Ribeiro; Lopes, Lorena Cristina Curado (International Journal of Movement Science and Rehabilitation, 2020)
Currently, several evidences demonstrate that the practice of resistance training (TR) promotes hypertrophy and increased muscle strength with loads (kg) between 30-80% of 1 maximum repetition (1RM). However, although the training method with vascular occlusion (TOV) and low loads is widely used for these purposes, its efficiency is not fully consolidated. Therefore, the aim of the study was to verify the effects of training with vascular occlusion on hypertrophy and muscle strength. As a method, a literature review was carried out in the databases Pubmed, LILACS and Scielo with the following keywords: occlusion training, Kaatsu training, vascular occlusion, resistance training, blood flow restriction, Kaatsu training, resistance training. Articles available in Portuguese and English between 2000 and 2020 were included. The results showed that the TOV method is efficient to increase hypertrophy and muscle strength in different populations / situations using low loads. In addition, the physiological changes inherent in vascular occlusion are efficient in the rehabilitation and / or maintenance of muscle mass during periods of immobilization or inability to move the limb. However, training should be prescribed taking into account the individual’s specificity in order to avoid possible adverse effects.